Digital Age Education: The Technological Wave - Rahman, Priyanggo Karunia (Jurnal Sustainable, 2024)
Education has experienced a significant shift as technology has become more prevalent in our digital age. The objective of this study is to examine the impact of incorporating technology on the teaching and learning process within the contemporary educational setting. This research investigates the effects of digital technologies, such as online learning platforms and artificial intelligence, on educational experiences using a literature analysis and case study methodology. The research backdrop emphasizes the significance of adjusting to technology advancements in order to achieve the objective of a more comprehensive and flexible education. The research methodologies employed encompassed literature synthesis from many academic sources and empirical studies to substantiate the findings and analysis. The findings indicate that the incorporation of technology has increased the availability of educational resources and fostered more interactive communication between students and educators. Nevertheless, there are obstacles such as the disparity in access to digital resources among educational groups and the difficulty of integrating new technology into conventional curricula. The paper concludes by highlighting the importance of well-targeted education policies and implementation techniques in order to fully harness the potential of technology in enhancing global education standards